Konstitusi Sebagai Batas Diskresi Fiskal Presiden: Telaah Normatif Atas Inpres Nomor 1 Tahun 2025 - Harjo Prayitno, Isnu; Muslihul Aqqad, Giovani (Program Studi Hukum Universitas Pamulang, 2025)
Presidential Instruction (Inpres) No. 1 of 2025 mandates budget savings of up to Rp 306 trillion from the State Budget (APBN) and Regional Budgets (APBD) as a response to the country's fiscal pressures, including limited tax revenue and rising expenditures on infrastructure and subsidies. This policy emerges amid the post-pandemic economic conditions that require efficiency, yet from the perspective of constitutional law, it sparks profound debates regarding the limits of the president's authority in regulating fiscal efficiency. To what extent does the president possess discretionary authority to manage fiscal efficiency, and how does the constitution restrict this discretionary space to ensure it does not violate the fundamental principles of a state governed by law? This article employs a normative juridical research method with a constitutional approach and public policy analysis to explore these issues. The findings indicate that the president indeed has discretionary authority to issue administrative policies such as Inpres, but this authority must not contravene constitutional principles, particularly Article 23 and Article 34 of the 1945 Constitution, which emphasize the use of the budget for the prosperity of the people and the fulfillment of basic rights. Fiscal discretion should be positioned as a tool to enhance government accountability and transparency, rather than a means to reduce the fulfillment of citizens' basic rights such as education, health, and social security. Consequently, the constitution serves as a check and balance mechanism over the president’s actions in managing state finances, ensuring that efficiency does not compromise social justice.